SEKULARISASI DAN ISLAMISASI ILMU PENGETAHUAN - Hamiruddin, (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2022)
One of the topics that have become a hot topic of discussion among intellectuals is secularization, secularism, and Islamization in the field of science. Secularization is a movement to break the relationship between religion and culture. scientists hardly cuddled. On that basis, secularism is considered teaching that does not have a strong foundation in Islam, either in its concept or in its movement, therefore knowledge of secularism needs to be understood by Muslims so as not to get caught up in secularism or secularization. In its later developments, there emerged an Islamization of science that described various efforts in various fields of modern thought. The final product is realized a new agreement for Muslims in the field of science that is appropriate and the scientific method and does not conflict with Islamic norms.